(untitled) (South Asian Journal of Agriculture, 2019)
The objectives of this study were to analyze the present scenario of tomato production and to explore the relationship between personal characteristics of the respondents and the problems confronted by them. Data were collected from randomly selected 50 respondents of five villages viz. Raingamari, Sachibunia and Dorgatola of Bathiaghata upazila and Mirzapur and Baratia of Dumuria upazila of Khulna district through personal interview method using an interview schedule during 11 March to 23 April, 2018. Problems confronted by the farmers were the dependent variable and the seven selected characteristics of the respondents considered as the independent variables. Most of the farmers (80%) possessed medium high land but majority of them (68%) bought small and marginal amount of land under vegetable and tomato cultivation respectively. The farmers cultivate Surakkha (80%) varieties followed by Guli (21%) and Paltola (18%). Fruit borer (62%) and wilting (70%) was the most prevalent insect and disease of tomato respectively. About half of the respondents (48%) fell into high problem confrontation category as compared to that of medium (32%) and low (20%) category. High cost of materials (86.67%) was the most reported severe problem while unavailability of labors (22.67%) was the least severe problem. Among the seven selected characteristics of the respondents, annual family income and area of land under tomato cultivation showed a negative significant relationship with their problem confrontation. South Asian J. Agric., 7(1&2): 51-55